(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
Al2O3 and Fe2O3 has been added as a nanoparticles (200 nm) 2.5 wt.%, to study their effects on microstructure and mechanical properties of pure Al by casting. Nanotechnology is now taking new processes to enhance the strength of metals and plastics. Lately, the remarkable magnetic, electric, optical, and catalytic capabilities of metal oxide nanoparticles like Al2O3 and Fe2O3 have received a lot of attention. Examination of microstructure, hardness, wear, and tensile has been conducted. All the data showed that adding nanoparticles had a significant impact on the properties compared with the properties of pure Al; for example, hardness increased by (20, 53)%, and volume wear loss by (27.7, 69.7)%. Moreover, increasing reach to (82, 254)% in UTS and (52, 107)% in yield point. These outcomes result from significant microstructural improvement (refining of grain size).